Study of Water Management Development in Petung Swamp Areas at the Province of East Kalimantan - Pramono, Agus Adi; Sisno, Suhardjono; Sholichin, Moch (Fakultas Teknik UB, 2021)
Swamp area is usually seen at the debouchment that is close to the sea. Swamp area can be used for farming area if it has a proper water management system. However, water management at the swamp area is hard to do and can be potentially become over drained in some areas. The aim of this study is to locate the potential areas that are able to occur over drained at Petung Swamp Irrigation System and able to find solutions of the problems. The first step to do is doing survey to know the condition of the channel, finding hydrological data, and tidal data. The hydrological data are intended to get modulus drain discharge. The next step is running data with HecRAS application to get the result of water channel profile of all channels. After that, analyzing the groundwater level could be done and meet the conclusion whether the channel is having over drained or not. The result of this study is the areas of Petung Swamp Irrigation that mostly having over drained condition are at the headwaters because the tide cannot reach the upper areas. The areas also have no floodgates, so the water journey couldnâ€™t be occurred and not evenly distributed.Â